Pharmacological inhibition of MyD88 suppresses inflammation in tubular epithelial cells and prevents diabetic nephropathy in experimental mice - Zhang Qiu-yan; Xu Su-jing; Qian Jian-chang; Yang Li-bin; Chen Peng-qin; Wang Yi; Hu Xiang; Zhang Ya-li; Luo Wu; Liang Guang (Acta Pharmacologica Sinica, 2022)
Emerging evidence shows that chronic inflammation mediated by toll-like receptors (TLRs) contributes to diabetic nephropathy. Myeloid differentiation primary-response protein-88 (MyD88) is an essential adapter protein of all TLRs except TLR3 in innate immunity. It is unclear whether MyD88 could be a therapeutic target for diabetic nephropathy. Here, we used a new small-molecule MyD88 inhibitor, LM8, to examine the pharmacological inhibition of MyD88 in protecting kidneys from inflammatory injury in diabetes. We showed that MyD88 was significantly activated in the kidney of STZ-induced type 1 diabetic mice in tubular epithelial cells as well as in high glucose-treated rat tubular epithelial cells NRK-52E. In cultured tubular epithelial cells, we show that LM8 (2.5−10 μM) or MyD88 siRNA attenuated high-concentration glucose-induced inflammatory and fibrogenic responses through inhibition of MyD88-TLR4 interaction and downstream NF-κB activation. Treatment with LM8 (5, 10 mg/kg, i.g.) significantly reduced renal inflammation and fibrosis and preserved renal function in both type 1 and type 2 diabetic mice. These renoprotective effects were associated with reduced MyD88-TLR4 complex formation, suppressed NF-κB signaling, and prevention of inflammatory factor expression. Collectively, our results show that hyperglycemia activates MyD88 signaling cascade to induce renal inflammation, fibrosis, and dysfunction. Pharmacological inhibition of MyD88 may be a therapeutic approach to mitigate diabetic nephropathy and the inhibitor LM8 could be a potential candidate for such therapy.